Circularly Polarized Luminescence in Nanoassemblies: Generation, Amplification, and Application. Issue 41 (8th August 2019) - Sang, Yutao; Han, Jianlei; Zhao, Tonghan; Duan, Pengfei; Liu, Minghua
Abstract: Currently, the development of circularly polarized luminescent (CPL) materials has drawn extensive attention due to the numerous potential applications in optical data storage, displays, backlights in 3D displays, and so on. While the fabrication of CPL‐active materials generally requires chiral luminescent molecules, the introduction of the "self‐assembly" concept offers a new perspective in obtaining the CPL‐active materials. Following this approach, various self‐assembled materials, including organic‐, inorganic‐, and hybrid systems can be endowed with CPL properties. Benefiting from the advantages of self‐assembly, not only chiral molecules, but also achiral species, as well as inorganic nanoparticles have potential to be self‐assembled into chiral nanoassemblies showing CPL activity. In addition, the dissymmetry factor, an important parameter of CPL materials, can be enhanced through various pathways of self‐assembly. Here, the present status and progress of self‐assembled nanomaterials with CPL activity are reviewed. An overview of the key factors in regulating chiral emission materials at the supramolecular level will largely boost their application in multidisciplinary fields. Abstract : Recent development of circularly polarized luminescent (CPL) materials has aroused extensive attention. The self‐assembly strategy is proposed to address the barriers of tedious syntheses and the restricted substitutes during the development of CPL‐active materials. By highlighting the meritorious findings, the present status and progress in this field are reviewed, with the aim of boosting the development of chiroptical materials.